Price competition, business hours, and shopping time flexibility - Oz Shy; Rune Stenbacka (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
We analyze differentiated retail industries where shops engage in two-stage competition with respect to opening hours and prices. We explore the effects of consumers' shopping time flexibility by comparing bi-directional consumers with forward- or backward-oriented consumers, who can either postpone or advance their shopping, but not both. We demonstrate that retailers with longer opening hours charge higher prices and that opening hour differentiation softens price competition. We calculate both symmetric and asymmetric subgame perfect equilibria in closing hours and demonstrate how the equilibrium configurations depend on the cost increases associated with extended business hours, as well as the relative densities of day and night shoppers. – – Wir analysieren unterschiedliche Einzelhandelsindustrien, in denen Läden in einem zweistufigen Wettbewerb bezüglich Öffnungszeiten und Preisen stehen. Wir erforschen die Effekte von Kundenflexibilität, indem wir völlig flexible Kunden mit vor- bzw. rückwärtsorientierten Kunden vergleichen können, welche ihren Einkauf nur vorziehen oder verschieben können, aber nicht beides. Wir zeigen, dass Einzelhändler mit längeren Öffnungszeiten höhere Preise verlangen und dass die Differenzierung der Öffnungszeiten den Preiswettbewerb abschwächt. Wir berechnen sowohl symmetrische als auch unsymmetrische teilspielperfekte Gleichgewichte für die Öffnungszeiten und zeigen, wie die Ausgestaltung der Gleichgewichte von den zusätzlichen Kosten der ausgedehnten Öffnungszeiten und der relativen Dichte von Tag- und Nachteinkäufern abhängt.
Keywords: L1; L81; M2; 330; Business Hours; Delayed or Advanced Shopping; Differentiated Business Hours; Price Competition; Shopping Time Flexibility